Problem-Solving On Numeracy Literacy Problems Based On Polya’s Theory In Terms Of Habits Of Mind - Hadi, Luthfia; Suhendra, Suhendra (Universitas Wiralodra, 2025)
Problem-solving abilities are one of the requirements that must be owned in facing the 21st century. In order for the problem-solving ability to be owned by everyone, it needs to be developed from school age. However, in fact, students' problem-solving ability is still low, especially in solving numeracy literacy problems. In addition, to prove problem-solving ability, habits of mind are needed as an attitude that allows individuals to develop behavioral intelligence based on stimulus in the process of solving problems. This study aims to describe and analyze students' problem-solving ability in solving numeracy literacy problems based on Polya's Theory in terms of habits of mind. The research questions are: 1) How is the problem-solving ability of students who have high habits of mind? 2) How is the problem-solving ability of students who have moderate habits of mind? and 3) How is the problem-solving ability of students who have low habits of mind? The subjects of this study were 28 eighth-grade students in one of the junior high schools in Bandung City, West Java. Data collection in this study used numeracy literacy problem-solving ability tests, habits of mind questionnaires, and interview guidelines to confirm the problem-solving ability tests and habits of mind questionnaires. The analysis results showed that: 1) Students with high habits of mind have high and moderate problem-solving ability; 2) Students with medium habits of mind have high and medium problem-solving ability; and 3) Students with low habits of mind have medium and low problem-solving ability.